Gross Capital Flows : Dynamics and Crises - Broner, Fernando; Didier, Tatiana; Erce, Aitor; Schmukler, Sergio L. (2012)
This paper analyzes the joint behavior of international capital flows by foreign and domestic agents -- gross capital flows -- over the business cycle and during financial crises. The authors show that gross capital flows are very large and volatile, especially relative to net capital flows. When foreigners invest in a country, domestic agents tend to invest abroad, and vice versa. Gross capital flows are also pro-cyclical, with foreigners investing more in the country and domestic agents investing more abroad during expansions. During crises, especially during severe ones, there is retrenchment, that is, a reduction in both capital inflows by foreigners and capital outflows by domestic agents. This evidence sheds light on the nature of shocks driving capital flows and helps discriminate among existing theories. The findings seem consistent with shocks that affect foreign and domestic agents asymmetrically, such as sovereign risk and asymmetric information.